Endocannabinoid receptor CB2R is significantly expressed in aspirin‐exacerbated respiratory disease: a pilot study. Issue 10 (13th June 2018) - Corrado, Alessia; Battle, Monica; Wise, Sarah K.; Lee, F. Eun‐Hyung; Guidot, David M.; DelGaudio, John M.; Molina, Samuel A.; Levy, Joshua M.
Abstract : Background: The endocannabinoid system represents a highly conserved, innate signaling network with direct and indirect control of eicosanoid‐mediated inflammation. Activation of the type 2 cannabinoid receptor (CB2R) leads to decreased type 2 inflammation and reduced production of arachidonic acid (AA). Given that altered AA metabolism is associated with aspirin‐exacerbated respiratory disease (AERD), we hypothesized that expression of the CB2R gene CNR2 is increased in AERD. Methods: Nasal polyps from consecutive patients undergoing endoscopic sinus surgery for AERD or allergic fungal rhinosinusitis (AFRS) were prospectively evaluated. Control sphenoid mucosa was collected from patients undergoing endoscopic skull base procedures. Expression and localization of endocannabinoid receptors were evaluated by quantitative reverse transcript–polymerase chain reaction (qRT‐PCR) and immunohistochemistry. A 2‐group unpaired t test with unequal variances was used to evaluate group differences. Results: Thirteen subjects were included in this pilot study, including 5 controls, 5 AFRS patients, and 3 AERD patients. Upregulated expression of CNR2 was detected in subjects with AERD vs both AFRS ( p = 0.049) and controls ( p = 0.047), with a mean increase of 5.2‐fold. No significant differences in expression of the CB1R gene CNR1 were detected between control and AFRS groups. Immunohistochemistry predominantly localized CB1R and CB2R expression to the surface epithelium in all subjects. Conclusion: The endocannabinoid system is an emerging immunomodulatory network that may be involved in AERD. This is the first study of CB2R in sinonasal disease, showing significantly increased transcription in nasal polyps from subjects with AERD. Additional study is warranted to further evaluate the contribution and therapeutic potential of this novel finding in chronic rhinosinusitis.